INSTRUCTIONAL PRACTICES IN ONLINE LEARNING: REFLECTION FOR TEACHER PROFESSIONAL DEVELOPMENT - Lasito Lasito; Susan Ayu Hidayat; Magpika Handayani (STKIP Persada Khatulistiwa Sintang, 2023)
As online education is in a growing demands these days, however, shifting roles from face to face to online teaching is considerably problematic. This paper explores teachers’ instructional practices in their efforts to assimilate with online teaching. Using questionnaires and interviews, this study elicited teachers’ strategies to adjust their instructional practices in online learning. Pedagogical strategies to guide students’ knowledge and scaffolding were becoming their main concern besides effective communication – through their lexical choices when giving instructions. This study also shed lights on teacher professional development they had received to prepare them for online learning and areas of professional development they expected to have to support their new roles in online educations. While most of the professional development groundwork was to do with technical issues, they also claimed that pedagogical and content knowledge were in needs for their continuous professional development.